A Young Massive Stellar Population Around the Intermediate Mass Black Hole ESO 243-49 HLX-1 - Farrell, S; Servillat, M; Pforr, J; Maccarone, T; Knigge, C; Godet, O; Maraston, C; Webb, N; Barret, D; Gosling, A; Belmont, R; Wiersema, K (2011)
We present Hubble Space Telescope and simultaneous Swift X-ray telescope observations of the strongest candidate intermediate mass black hole ESO 243-49 HLX-1. Fitting the spectral energy distribution from X-ray to near-infrared wavelengths showed that the broadband spectrum is not consistent with simple and irradiated disc models, but is well described by a model comprised of an irradiated accretion disc plus a stellar population with a mass ~1E6 Msun. The age of the population cannot be uniquely constrained, with both very young and very old stellar populations allowed. However, the very old solution requires excessively high levels of disc reprocessing and an extremely small disc, leading us to favour the young solution with an age of ~13 Myr. In addition, the presence of dust lanes and the lack of any nuclear activity from X-ray observations of the host galaxy lead us to propose that a gas-rich minor merger may have taken place less than ~200 Myr ago. Such a merger event would explain the presence of the intermediate mass black hole and support a young stellar population.